Development and Evaluation of Photoprotective O/W Emulsions Containing Hydroalcoholic Extract of Neoglaziovia variegata (Bromeliaceae) - Raimundo Gonçalves de Oliveira-Júnior; Grasielly Rocha Souza; Christiane Adrielly Alves Ferraz; Ana Paula de Oliveira; Camila de Souza Araújo; Sarah Raquel Gomes de Lima-Saraiva; Silvio Alan Gonçalves Bomfim Reis; Talita Mota Gonçalves; Larissa Araújo Rolim; Pedro José Rolim-Neto; Francine Celise Siqueira César; Jackson Roberto Guedes da Silva Almeida (The Scientific World Journal)
Neoglaziovia variegata is a Bromeliaceae plant species widely found in Brazil with several pharmacological properties, including photoprotective activity. Although herbal-based active ingredients have been applied in cosmetic products, especially for skin treatment, its application in sunscreen formulations remains unexplored. The aim of this work is to evaluate the photoprotective effect of cosmetic formulations containing hydroalcoholic extract of N. variegata (Nv-HA). Initially, the phenolic and flavonoid total content of Nv-HA were determined. The photoprotective activity of Nv-HA was subsequently assessed using a spectrophotometric method. Nv-HA was incorporated in O/W emulsions in the presence or absence of synthetic filters and their photoprotective efficacy was evaluated by spectrophotometric SPF determination. Finally, the stability study of the formulations was performed through the freezing/defrosting method. Nv-HA showed significant phenolic and flavonoids content (61.66±5.14 mg GAE/g and 90.27±5.03 mg CE/g, resp.). Nv-HA showed SPF values of 5.43±0.07 and 11.73±0.04 for the concentrations of 0.5 and 1.0% (v/v), respectively. It was verified that Nv-HA potentiated the photoprotective effect of formulations containing only synthetic filters. Furthermore, the formulations have remained stable at the end of the preliminary stability study. According to the results, it was concluded that Nv-HA can be used as a chemical filter in cosmetic formulations.